Pengaruh Perilaku Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Di Lingkungan Kecamatan Purbaratu Kota Tasikmalaya - Riza Muhammad Dimyati; Arga Sutrisna; Nita Fauziah Oktaviani (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
This research was conducted with the aim of knowing the effect of work behavior and work discipline on employee performance in the Purbaratu District Tasikmalaya City. The method used in this study was a survey method using data obtained directly through questionnaires distributed to 55 respondents who were employees in the Purbaratu District, Tasikmalaya City. The technique used in this research is multiple regression analysis. Based on the research results, it is known that work behavior and work discipline simultaneously have a positive and significant effect on employee performance in the Purbaratu District, Tasikmalaya City. Work behavior partially has a positive and significant effect on employee performance in the Purbaratu District, Tasikmalaya City. Work Discipline partially has a positive and significant effect on Employee Performance in the Purbaratu District, Tasikmalaya City.